2006
DOI: 10.1111/j.1749-7345.2006.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Plant‐protein‐based Diets Supplemented with Yucca on Growth, Digestibility, and Chemical Composition of Nile Tilapia (Oreochromis niloticus, L) Fingerlings

Abstract: Replacement of fish meal (FM) protein with dehulled and solvent‐extracted plant by‐products, soybean meal, cottonseed meal, sunflower meal, and linseed meal was tested in diets for juvenile Nile tilapia, Oreochromis niloticus. Fish averaging (±SD) 14.2 ± 2.9 g were divided into 18 groups and fed for 6 mo on pelleted feed containing each of the plant protein meal supplemented with Yucca schidigera powder extract at 750 mg/kg. Methionine (1%) and lysine (0.5%) were added to each diet except the control diet (FMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 16 publications
(16 reference statements)
3
39
1
2
Order By: Relevance
“…Several studies have demonstrated similar encouraging results in the biological performance while replacing fish meal in diets for tilapia, using either single ingredients to replace it (Soybean meal: Shiau et al 1987Shiau et al , 1989Deyab and El-Saidy 2002;Gaber 2006. Sunflower seed meal: Olvera-Novoa et al 2002;Gaber 2006.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have demonstrated similar encouraging results in the biological performance while replacing fish meal in diets for tilapia, using either single ingredients to replace it (Soybean meal: Shiau et al 1987Shiau et al , 1989Deyab and El-Saidy 2002;Gaber 2006. Sunflower seed meal: Olvera-Novoa et al 2002;Gaber 2006.…”
Section: Discussionmentioning
confidence: 96%
“…Linseed meal: Gaber 2006. Cottonseed meal: El-Sayed 1990Mbahinzireki et al 2001;Gaber 2006) or mixtures of numerous plant protein sources (El-Saidy and Gaber 2003;Borgeson et al 2006). The SGR attained in this study (1.04-1.57% day -1 ) are comparable to other values reported by Mbahinzireki et al (2001) ranging from 1.0 to 1.4% day -1 when dietary fish meal was replaced by cottonseed meal, or by El-Saidy and Gaber (2003), with SGR ranging from 1.4 to 1.6% day -1 when they replaced fishmeal by a mixture of plant protein sources.…”
Section: Discussionmentioning
confidence: 99%
“…BG and CONT diets showed no significant differences in case of the whole body crude lipid content. Gaber (2006) reported the higher body protein content in Nile tilapia fed the Yucca-supplemented diet compared with the control diet and significantly lower body lipid content than that of the control diet. Similarly, Yilmaz et al (2012) also reported lower crude lipid content in sea bass Dicentrarchus labrax fed the herbal extracts compared with the control diet.…”
Section: Whole Body Proximate Analysismentioning
confidence: 92%
“…Yucca extracts have been found to promote growth, improve immune system, antimicrobial ability and stimulate appetite and anti-stress characteristics. Inclusion levels of yucca extract in aqua feeds include: 0.075% (Gaber 2006) and 0.1-0.58% for Nile tilapia (Njagi et al 2017), 0.1% for striped catfish (Güroy et al 2014). The b-glucan (BG) is an inactivated natural microbial product that is also recognized for its immunomodulatory roles in aquatic organisms (NRC 2011).…”
mentioning
confidence: 99%
“…Increasing fishmeal cost, irregular supply, decreasing availability, and poor quality of fishmeal have put forward highlighting on its partial or complete substitution with other alternative protein sources (Ramachandran and Ray, 2007). Currently, a lot of studies have been conducted to assess the partial or complete substitution of fishmeal in feed diets for tilapia with less expensive as well as locally available plant and animal protein sources (Fasakin et al, 2005;Borgeson et al, 2006;Gaber, 2006;Goda et al, 2007;Schuchardt et al, 2008;Soltan et al, 2008;Ali et al, 2008;Metwally and El-Gellal, 2009;Mohammad and Abdel-Tawwab, 2011;Labib et al, 2012;Abo-State et al, 2014;Hassan et al, 2015;Labib et al, 2015;Yones and Metwalli, 2015;Sharawya et al, 2016;Al-Asgah et al, 2016;. The review in hands aims to appraise the diverse types of fishmeal substituents and draw attention to the most proper alternatives in fish diets.…”
Section: Introductionmentioning
confidence: 99%